(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to find out what influences social responsibility, , in the correlation between social responsibility and the strategic vision through the two main hypotheses This research presented a problem that is the lack of realization of the relationship between the strategic orientation and social responsibility, which seeks to achieve social welfare and a better life for society in its various categories. Thus, modern organizations seek to apply ideas and mechanisms according to considerations of development and renewal of the work environment of these organizations, which makes them more in need of employing the orientation. Strategic in performing its tasks, functions and operations because of its positive and effective advantages that are reflected in the organization such as harnessing mental capabilities and behavioral skills in solving problems. The importance of the research came from the importance of the topic it deals with and the research elements that sought to address it and the size of the impact they have on the overall environment This research presented the most important findings of researchers, writers, and some Arab and foreign studies in the banking field, The research concluded with the most prominent results, the most important of which was (the existence of a significant correlation and influence between the strategic orientation in achieving social responsibility in its dimensions).